Consequences of cross-cultural differences in perceived well-being for entrepreneurship - Pathak, Saurav; Muralidharan, Etayankara (My University, 2021)
In this article, we empirically test a theory-based model that delineates the indirect effect of societal-level well-being, through societal-level self-expression values, on individual entrepreneurship. Using 881,636 individual-level responses obtained from the Global Entrepreneurship Monitor (GEM) from 44 countries and supplementing with country-level data from the World Values Survey (WVS), our results from multilevel cross-cultural analyses demonstrate that societal-level well-being - hedonic and eudaimonic - are positively related to societal-level self-expression values, and that self-expression values mediate the relation between both types of well-being and likelihood of individuals engaging in entrepreneurship. Hence, hedonic and eudaimonic well-being are distal whereas self-expression values are more proximal influencers of individual entrepreneurship. We discuss theoretical and practical implications of our findings.
Keywords: eudaimonic; hedonic; well-being; self-expression; entrepreneurship